Borromean rings redux. A missing link found – a Borromean triplet of Borromean triplets. Issue 2 (17th February 2023) - O'Keeffe, Michael; Treacy, Michael M. J.
Abstract : A nine‐component Borromean triplet of Borromean triplets is described. Abstract : This paper describes a nine‐component Borromean structure – a Borromean triplet of Borromean triplets – that was missing from an earlier enumeration.